2014
DOI: 10.1200/jco.2013.53.3604
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma mRNAs Predict Outcome in Children With Stage 4 Neuroblastoma: A European HR-NBL1/SIOPEN Study

Abstract: High levels of TH and PHOX2B mRNA in PB at diagnosis objectively identify children with ultrahigh-risk disease who may benefit from novel treatment approaches. The level of TH, PHOX2B, and DCX mRNA in BM and/or PB at diagnosis might contribute to an algorithm to improve stratification of children for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
141
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(147 citation statements)
references
References 32 publications
4
141
1
1
Order By: Relevance
“…However, our study showed that outcomes within the high-risk group differ according to TH expression in PB at diagnosis. Previous studies also reported that positive TH expression was a poor prognostic indicator in metastatic NB [13,21,22]. These findings suggest that TH expression at diagnosis might be a significant factor in future methods of risk stratification for NB.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, our study showed that outcomes within the high-risk group differ according to TH expression in PB at diagnosis. Previous studies also reported that positive TH expression was a poor prognostic indicator in metastatic NB [13,21,22]. These findings suggest that TH expression at diagnosis might be a significant factor in future methods of risk stratification for NB.…”
Section: Discussionsupporting
confidence: 56%
“…These ultrahigh-risk patients showed very poor outcome among the group of high-risk NB patients (PFS, 0%), most of whom underwent single HDCT/auto-SCT following short induction treatment. The authors suggested that patients with very high TH expression are candidates for alternative treatment strategies [22]. In the current study, the prognosis of patients with high TH expression was also poorer than for those with low TH expression, but was not dismal.…”
Section: Discussionmentioning
confidence: 48%
“…Here we show that mutations in FA and RAC pathways (promoting metastasis and cancer progression) occur frequently in a subset of unfavourable neuroblastoma and confirm this finding in three independent sets of neuroblastoma samples. A recent study has suggested that dysfunction of FA pathway promotes bone marrow infiltration of stage 4 neuroblastoma [2]. Importantly, anticancer compounds targeting FA and RAC pathways can reduce growth, motility and viability of tumor cells in neuroblastoma [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although many low and intermediate-risk patients are amenable to no or little therapy, overall survival rates of patients diagnosed as high-risk tumors remain below 50% despite receiving complex and intensive treatments [1]. Among high-risk patients, gene signatures can identify children with higher risk disease who would benefit from new and more aggressive therapeutic approaches [2]. Genome-wide association studies have identified multiple DNA polymorphisms influencing neuroblastoma susceptibility and clinical phenotype [3-7].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several mRNA and miRNA classifiers have been established [11-13]. A recent study from SIOPEN shows that levels of tyrosine hydroxylase ( TH ) and paired-like homeobox 2B ( PHOX2B ) or doublecortin ( DCX ) mRNA in peripheral blood and bone marrow at diagnosis are independent predictors of survival [14]. Notably, high levels of TH and PHOX2B mRNA in peripheral blood identify ultrahigh-risk NB patients.…”
Section: Introductionmentioning
confidence: 99%